Facile preparation of fluorescent carbon dots for label-free detection of Fe3+ - Jayaweera, Supuli (2021)
Cellulose is the most abundant biomass resource and use of cellulose in the synthesis of novel nanomaterials like carbon dots (CDs) has gained attention over the years. However, the photoluminescence yield of cellulose-based CDs is low in the absence of modification additives. Durian shell waste (DSW) is a cellulose rich source and is used for the first time in a one-pot process without any modification agent to produce CDs. The presence of carboxylic acids, esters and amino compounds in durian shell was crucial to improving the CD surface and resulting in a mass yield of 13.9% and quantum yield of 6.2%. This was two times higher compared to that of CDs derived from pure cellulose precursors. The blue-green emitting CDs showed stability over a wide range of pH and chloride concentration and was resistant to photobleaching. Further, the CDs showed high selectivity towards Fe3+ by forming a non-fluorescent ground complex with the oxygen functional groups. Based on the linear relationship between normalized fluorescence intensity and concentration of Fe3+ ions, the synthesised CDs may be used as a fluorescent probe to detect Fe3+ over a concentration range of 0–20 μM with a detection limit of 128 nM. The method was successfully applied in sensing Fe3+ in actual water systems.